[11C]Fluoroform, a Breakthrough for Versatile Labeling of PET Radiotracer Trifluoromethyl Groups in High Molar Activity. Issue 34 (17th May 2017) - Haskali, Mohammad B.; Pike, Victor W.
Abstract: Positron‐emission tomography (PET) is an immensely important imaging modality in biomedical research and drug development but must use selective radiotracers to achieve biochemical specificity. Such radiotracers are usually labeled with carbon‐11 ( t 1/2 =20 min) or fluorine‐18 ( t 1/2 =110 min), but these are only available from cyclotrons in a few simple chemical forms. [ 18 F]Fluoroform has emerged for labeling tracers in trifluoromethyl groups but is severely limited in utility by low radioactivity per mass (low molar activity). Here, the synthesis of [ 11 C]fluoroform is described, based on CoF3 ‐mediated fluorination of cyclotron‐produced [ 11 C]methane. This process is efficient and repetitively reliable. [ 11 C]Fluoroform shows versatility for labeling small molecules in very high molar activity (>200 GBq μmol −1 ), far exceeding that possible by using [ 18 F]fluoroform. Therefore, [ 11 C]fluoroform represents a major breakthrough for labeling prospective PET tracers in trifluoromethyl groups at high molar activity. Abstract : Putting a label on it : Cobalt(III) fluoride mediates efficient transformation of cyclotron‐produced [ 11 C]methane into [ 11 C]fluoroform with high molar activity. [ 11 C]Fluoroform shows broad utility as an efficient labeling synthon for prospective positron emission tomography (PET) radiotracers.